Nanomolar resveratrol reduces early alterations of pancreatitis and pancreatic cancer in pancreatic acinar cells - Thiago M.C. Pereira; Glaucimeire R. Carvalho; María Luaces-Regueira; Ana Bugallo-Casal; Ana Iglesias-Mejuto; Lonneke Nugteren; Martina Schmidt; Dolores Viña; Elisardo C. Vasquez; Manuel Campos-Toimil (Elsevier, 2022)
Resveratrol is a natural phytoalexin present in human diet with a potential beneficial effect in many diseases including chronic and acute pancreatitis, a potentially fatal disease with significant morbimortality accompanied with obscure pathogenesis and without effective treatments. Resveratrol has also been shown to be a promising anti-tumor molecule on the millimolar scale. In this study, the protective effects of nanomolar concentrations of resveratrol against early events common to pancreatic cancer and pancreatitis induced by supra-physiological concentrations of cholecystokinin (CCK, 100 nM) were evaluated. Resveratrol (200, 500 nM) reduced CCK-induced intracellular trypsin activation and cell injury in isolated rat pancreatic acinar cells (PAC). The damage induced by high CCK and the protective effect of resveratrol was also measured in pancreatic tissue explants by analyzing histological changes. Finally, the effect of resveratrol on the CCK-enhanced nuclear factor κB (NF-κB) expression was studied by Western blot experiments in the AR42J pancreatic acinar cell line. Our results show, for the first time, the ability of resveratrol to reduce premature intracellular activation of trypsin and necrosis in PAC. It is suggested that resveratrol counteracts CCK-induced pancreatic tissue breakdown by downregulation of NF-κB in the nuclear fraction. Since these effects occur at nanomolar concentrations that can be achieved by oral intake, our results suggest that dietary consumption of resveratrol could have a preventive effect and delay the evolution of pancreatitis and pancreatic cancer.